STUDI IDENTIFIKASI PLANKTON DI MUARA SUNGAI TALLO KOTA MAKASSAR - Patang Patang; Andi Puspa Sari Idris (Jurnal Pendidikan Teknologi Pertanian, 2022)
The study aimed to identify the level of diversity of phytoplankton and zooplankton around Muara Tallo, Makassar. The study was conducted for 3 months, namely May to July 2018, in three observation stations, namely location 1 which is located around the mangrove forest, location 2 is located around the estuary of the Tallo River and location 3 which is located around Paotere Harbor, Makassar. Plankton sampling is carried out in the morning using plankton net No. 25. Plankton samples are then taken to the laboratory for identification and analysis.The results showed that when sampling at station 1 there were species of Leptocylidricus sp. Phytoplankton, and Cosvinodiscus sp. and Pleurosigma sp., Paralia sp., Bacillaria sp., but Chaetoceros sp. not found on this station. At the Station 2 phytoplankton species found were Cosvinodiscus sp. and Leptocylidricus sp., then Pleurosigma sp. and at station 3 phytoplankton can be found namely phytoplankton  of Leptocylidricus sp., and Cosvinodiscus sp. While station 1 found abundance of phytoplankton, namely the type of Leptocylidricus sp. and Cosvinodiscus sp. Station 2 abundance of types of Leptocylidricus sp., Cosvinodiscus sp. Pleurosigma sp. and Paralia sp. while station 3 is the abundance of phytoplankton in Leptocylidricus sp., Cosvinodiscus sp., Bacillaria sp. and Chaetoceros sp.